MONITORING OF INFORMATION PROCESSES OF ENTERPRISES AS THE BASES OF FORMING KNOWLEDGE ECONOMY AT REGIONAL LEVEL - Podluzhna , N. O. (The actual problems of regional economy development, 2018)
Achieving the state of knowledge economy at the regional level is possible only under the condition of active use of information and communication technologies in the production and commercial activities of enterprises. The purpose of the study is to determine the state of the processes of information of enterprises in order to assess the potential opportunities for the establishment of knowledge economy in the regions of Ukraine. The object of the research is the processes of information, which are inherent in the production and commercial activity of enterprises. In order to achieve this goal, methods of data compilation and grouping, tabular and graphical methods are used. The tendencies in the processes of information and business computerization, the attraction of personnel to the new technologies, the use of local and large-scale corporate networks, and the use of the Internet network are revealed. Measures have been proposed to increase the efficiency of information processes at enterprises in order to facilitate the fastest formation of knowledge economy in the country and regions.